Library and data management support for interdisciplinary research among faculty members in Nigerian universities - Oladokun, Bolaji; Dumbiri, Rita; Nelson, Etido; Etefia, Etido (Knowledge Garden: International Journal of Library Studies, 2025)
Purpose: This study explores how libraries support data management in interdisciplinary research, particularly the challenges that researchers face and the role libraries play in providing effective data management solutions. The study’s objectives were to identify the challenges interdisciplinary researchers encounter in managing data and to examine how libraries provide support for these data management needs. Design: A descriptive research design was employed to capture perspectives from faculty members engaged in interdisciplinary research at universities in Akwa Ibom State, Nigeria. The study targeted a population of senior academic staff, with a sample size of 200 faculty members. A convenient sampling approach selected Akwa Ibom State University and the Federal University of Technology, Ikot Abasi, as study sites. Data were collected using a structured questionnaire. Frequencies, percentages, means, and standard deviations, were used for data analysis. Findings: The findings indicate that interdisciplinary researchers face several challenges in data management, including data heterogeneity, communication barriers, variations in research methodologies, differences in terminologies, and ethical considerations. Additionally, the study reveals that libraries support data management through data management planning, data literacy training, data repository development, and guidance on best practices. However, limited resources and infrastructure sometimes constrain libraries’ effectiveness in these roles. The study emphasizes the essential role of libraries in providing RDM support but highlights the need for increased funding, resources, and training to maximize their impact on interdisciplinary research. Originality: The paper is one of the first to investigate the library and data management support for interdisciplinary research among faculty members in Nigeria. The study recommends that universities enhance data management training programs and that institutional stakeholders allocate more resources to libraries for improved RDM infrastructure and services.